Contrasts of power and political influence in two media: private and public in Ecuador, during the COVID -19 pandemic - Vásquez Calahorrano, Miguel; Serrano Moscoso, Shirley; Alvear Viteri, Andrea (Scripta Mundi, 2023)
The present study shows the journalistic treatment exposed by two media outlets, one of public service, administered by the state and the other private, on the health crisis that occurred in Guayaquil, Ecuador, at the highest peak of the pandemic caused by COVID-19., where high levels of contagion were evidenced, producing daily high numbers of deaths, this particular situation generated subsequent abandonment, loss and misplacement of corpses, caused among other things by the lack strategy of planning and government communication to face the crisis, reflected in the absence of official information, lack of protocols, plans to confront the pandemic, which is why it is essential to carry out an analysis of the editorial line of the media in relation to public and private communication, evidencing their interests, the same that contributed to generating fear among the population and hiding reality, affecting the credibility of the media. The methodology used was based on a quantitative review of the publications made by the media between March 13 and May 20, 2020, as a space for analysis, in addition, a survey applied to 50 journalists who work in that city, included in the chat called “Social Communicators” and interviews with professionals and academics who contributed with qualitative analysis.
Keywords: Media; credibility; COVID-19; pandemic